An analysis of the profitability and sustainability of savings and credit co-operatives in Botswana - Nthaga, Laone Gosego (Research of GSB, 2018)
Since the 2008 financial crisis, global attention has been drawn to co-operatives, owing to their resilience and ability to flourish during tough economic conditions. The potential of co-operatives as a catalyst for sustainable development is of particular interest to a country like Botswana, where the economy is heavily reliant on a single commodity trade and there is potential for greater participation of the citizens in economic and social development of the country. The growing participation of co-operatives, particularly savings and credit co-operatives (SACCOs), has proved to be a channel for increasing access to finance for the traditionally unbanked, a reduction in poverty levels, and continued socioeconomic development across the African continent. In Botswana, however, only 26% of co-operatives are profitable, while 30% operate at a loss or break even. This necessitates an empirical investigation into the performance (profitability and sustainability) of SACCOs in Botswana. Literature presents various views regarding the determinants of profitability of SACCOs; these include the selection of a skilled management committee, the clear articulation of and compliance with a credit policy, the presence of a savings culture in the area of operation, sound corporate governance, credit default rates, membership numbers and members' level of financial literacy. This study ascertains the key determinants of the profitability and sustainability of SACCOs in Botswana and the extent to which these factors influence the SACCOs' operational self-sufficiency (OSS). The population included 39 SACCOs from eight regions across the country. The independent variables chosen were return on assets, deposit mobilisation, current ratio, capital structure, and membership size. Panel data analysis for financial data collected over 10 years (2005 to 2015) for all registered SACCOs was used. The study revealed that return on assets and capital structure were significantly and positively related to OSS, which was generally consistent with literature. Size and liquidity were found to be statistically insignificant determinants of OSS. A finding unique to this study, and contrary to literature, was the negative relationship observed between deposit mobilisation and OSS. Informed by the findings of the study, the main recommendations are that members of SACCOs as well as regulators should ensure that management provides a clear investment strategy that shows consideration for revenue diversification. The Ministry of Investment, Trade and Industry should also channel resources into implementing supporting policies and legislature for SACCOs, such as the Co-operative Transformation Strategy, to enable these entities to thrive.